Adsorption kinetics and isotherms of penconazole, cyproconazole and epoxiconazole with chitosan (BISTUA Revista de la Facultad de Ciencias Básicas, 2021)
In the search for alternative technologies that can mitigate the contamination problem in water sources, mainly those destined for human consumption, the chitosan powder efficiency for the pesticide removal has been evaluated. In adsorption processes there is a wide spectrum of physical and chemical mechanisms, which normally occur in consecutive stages such as the diffusion of the adsorbate through the fluid film to the adsorbent material, diffusion through the pores and subsequent reaction of adsorption. In this process, it was observed that each analyte, depending on its physicochemical and / or structural properties, presented different adsorptions, which was confirmed observing to the variation in pesticide removal percentages using the same adsorbents quantities. The optimization of the removal variables allowed to determine that the maximization values for most analytes percentage removal are similar and close to the maximum values of contact time and amount of adsorbent. The adsorption kinetics study allowed to establish the equilibrium time, which was 180 minutes for the analytes, and the data modeling wich responded to a pseudo-second order kinetics. Regarding to the adsorption isotherms' modeling, the best fit model is Freundlich's. Faced with this complex issue, the evaluation of pesticide removal through technological processes becomes relevant in order to maintain the water resources availability with adequate quality.
Keywords: fungicides; adsorption; chitosan; isotherms